Dynamics of changes in the level of IgA in patients with bronchial asthma against the background of excessive body weight or obesity - Lahoda, Daria; Velychko, Valentyna (European Journal of Clinical and Experimental Medicine, 2019)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Among patients with asthma, a lot of attention is being given to, at the present time, to such comorbidity as excessive body mass (EBM) or obesity. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. To evaluate the level of IgA in patients with bronchial asthma against the background of excessive body weight or obesity and to evaluate the effects of drug on the bacterial lysate and inosine pranobex. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. According to the design, the study was conducted in two stages: the first stage – examination of 105 patients with asthma. 105 patients with a basic diagnosis of asthma were examined whose average age was 41.19 ± 1.05 years, 75 patients were found to have EBM or obesity (BMI 31.67 ± 0.53) who were included in the main group and 30 patients with NBMI (BMI 22.13 ± 0.32), which were the comparison group. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The patients in the main group with a severe course had significantly lower serum IgA values than the patients in the comparison group (p<0.05), but the statistically significant difference between this index in the patients with a severe course in the main group and the control group was not revealed. The patients in the main group had a significant increase in the level of secret IgA against the background of the use of treatment-and-prophylactic complex (TPC) with the inclusion of a preparation of bacterial lysate in combination with inosine pranobex against the background of training in asthma school, receiving the basic treatment (p<0.05). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Patients with asthma who have large BMI have a more severe course of bronchial asthma. A Correlation relationship was established in the group of patients with bronchial asthma and with excessive body weight or obesity between the level of sIgA and the severity of the asthma course; there is a direct strong correlation. Patients in the main group had a significant increase in the level of sIgA against the background of the use of TPC with the addition of a basic treatment by the preparation of bacterial lysate together with inosine pranobex.